PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VB SD NEGERI 27 SEBANGAR KECAMATAN MANDAU - Heniwidyawati Heniwidyawati; Lazim N Lazim N; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was conducted because of the result of learning social study class VB SD Negeri 27 Sebangar.From 30 students who can reach KKM only of 14 person (46,67%) over while the students who can’t complete 16 person ( 53,33%) with an average of 61,33. This research to increase study result IPS class VB SD Negeri 27 Sebangar with the model applied learning think pair share. The result research have reach average basic score 61,33 grow up on one cycle amount of 27,7% to 78,33%. purpose of this research to improve learning outcomes IPS class VB SD Negeri 27 Sebangar In the second cycle the average value of student also increased by 29,8% to 79,66%. On complete basic score,study result IPS only 53,33% ( students can’t complete). After applied learning model Think Pair Share (TPS) on one cycle have in the classical completed grow up to 76,67% (can’t complete), on the second cycle have classical complete can reach from the students grow up to 86,67%. Teacher activities on the first appoinments grow up to 81,25% with the exsellent category. The second meeting increased to 90,62% with the excellent category. On the second appointments second cycle grow up 93,75% with the excellent category. Of the second appointment second cycle, teacher avtivity grow up to 96,87% with the excellent category. Student activities on the first cycle students can reach presentation of 62,5% with the good category. On the second appointment on one cycle to 71,87% with the good category. On the second cycle first appointment students activity grow up to 87,5% with the excellent catgory, and on the second appointment second cycle back grow up to 96,87% with the excellent category.Key Words : Think Pair Share (TPS), Study result IPS